Multimodal Processing and Interaction Audio, Video, Text - Maragos, Petros; Potamianos, Alexandros; Gros, Patrick; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Multimodal Processing and Interaction: Audio, Video and Text presents high quality, state-of-the-art research ideas and results from theoretic, algorithmic and application viewpoints. This edited volume contains both state-of-the-art reviews and original contributions by leading experts in the scientific and technological field of multimedia. It grew out of a four-year collaboration among research groups participating in the European network of Excellence on Multimedia Understanding, Semantics, Computation and Learning (MUSCLE). Multimodal Processing and Interaction: Audio, Video and Text covers a broad spectrum of novel perspectives, analytic tools, algorithms, design practices and applications in multimedia science and engineering with emphasis on multimodal integration and modality fusion. This volume also contains contributions in the area of interaction with multimedia, especially multimodal interfaces for accessing multimedia content. Multimodal Processing and Interaction: Audio, Video and Text is designed for a professional audience composed of practitioners and researchers in industry and academia. This book is suitable for advanced-level students in computer science and engineering as well.
Review of the State of the Art -- Cross-Modal Integration for Performance Improving in Multimedia: A Review -- Human-Computer Interfaces to Multimedia Content a Review -- Integrated Multimedia Analysis And Recognition -- Stochastic Models for Multimodal Video Analysis -- Adaptive Multimodal Fusion by Uncertainty Compensation with Application to Audio-Visual Speech Recognition -- Action Recognition in Multimedia Streams -- Surveillance Using Both Video and Audio -- Movie Analysis with Emphasis to Dialogue and Action Scene Detection -- Audiovisual Attention Modeling and Salient Event Detection -- Toward the Integration of Natural Language Processing and Automatic Speech Recognition: Using Morpho-Syntax and Pragmatics for Transcription -- Searching Multimedia Content -- Interactive Image Retrieval Using a Hybrid Visual and Conceptual Content Representation -- Multimodal Analysis of Text and Audio Features for Music Information Retrieval -- Intelligent Search for Image Information on the Web through Text and Link Structure Analysis -- Interfaces to Multimedia Content -- IDesign Principles for Multimodal Spoken Dialogue Systems -- Eye Tracking: A New Interface for Visual Exploration -- User Interaction for Mobile Devices.
Keywords: Computer science; Computer communication systems; Information storage and retrieval; Multimedia information systems; Artificial intelligence; Computer graphics; Biometrics (Biology).; Computer Science; Artificial Intelligence (incl. Robotics).; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Biometrics; Information Storage and Retrieval; Computer Communication Networks; Electronic books